PESTEL Analysis of Smallholder Wool Producers for Improved Efficiency and Rural Livelihoods: A Case Study of The South African Wool Value Chain - Ntsiapane, Alina; Swanepoel, Jan; Nesamvuni, Azwihangwisi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
Wool production has great potential to alleviate food insecurity and poverty in South Africa, but declining national output poses significant challenges. The lack of comprehensive studies on macro-environmental factors and efficiency in smallholder wool farming hinders effective policymaking and resource allocation to improve sustainability. This study conducted a PESTEL analysis and introduced a model to improve the efficiency of smallholder wool farming and rural livelihoods through the evaluation of the industrial macro environment. The PESTEL analysis assisted farmers in identifying future macroeconomic variables to ensure the proper development and sustainability of their wool farming. The analysis uncovered a negative correlation between the efficiency of wool farming and the lack of access to information, markets and credit, feed costs, inadequate extension services, and farmers’ lack of knowledge. Consequently, this study advocated for the training of smallholder wool farmers to improve their wool quality, extension services, and access to information, markets, and credit. This research further proposed minimum operational and transaction costs to enhance the overall efficiency of smallholder wool production in Thaba ‘Nchu and Botshabelo.